The pCF10-encoded pheromone response: cell-cell signaling, complexity and evolution - Dunny, Gary (Henry Stewart Talks, 2008)
Overview of the evolutionary and medical significance of plasmids in E faecalis, Overview of cell-cell signaling and plasmid transfer, The sex pheromone system, Pheromone production and control plasmid pCF10 as a model for pheromone-controlled plasmid transfer, Mechanism of pheromone induction, Multiple roles for pheromone induction, Maintenance of complexity in evolution